Mapping the evolution of topics published by Education for Information: Interdisciplinary Journal of Information Studies - Ibekwe, Fidelia; Bochi, Fernanda [UNESP]; Martínez-Ávila, Daniel (SAGE Publications, 2021)
The need to map the evolution of trends in any field of activity arises when a large amount of data is available on that activity, thus making impossible a manual exploration of the data in order to understand how the field or the activity is evolving. Topic and trend mapping is a mature field with hundreds of publications on approaches, methods and tools for data collection, analysis, feature extraction and reduction, clustering and visualisation tools and algorithms. Our study aims to map the evolution of topics published by the journal Education for Information. Interdisciplinary Journal on Information Studies (EFI henceforth) which has been in existence since 1983, in order to understand how this journal has evolved and how it is positioned with regard to the field of Library and Information Science to which it belongs. Our study is part of the body of work on topic detection and text mining. Our results showed that the journal displayed a remarkable stability in its editorial policy over more than three decades. With the arrival of its third Editor in Chief in 2018, a shift towards more technologically oriented topics and to specialties from other fields are perceptible such as health information, data science and digital humanities.
Keywords: clustering; content analysis; emerging scientific structures; information science; noun phrase extraction; Topic mapping; trends survey